Professional training in organic food production: a cross-country experience - Guiné, Raquel (2017)
Purpose: The aim of this work was to characterize the agricultural activities and past experience in professional training in the context of mobile learning in different countries (Portugal, Spain, Slovakia, Hungary, United Kingdom, Italy and Turkey). Design: For the survey, a questionnaire was prepared in English and Portuguese and then translated into the languages of the participating countries. It was delivered electronically for answering on-line by adults only. The participation was voluntary and in the end 133 consented valid questionnaires were obtained. For the treatment of the data was used SPSS and basic descriptive statistics tools were applied, together with tests, namely crosstabs and chi square tests, considering a level of significance of 5%. Findings: The results showed that the majority of the participants presently have some agricultural activity and one third is thinking about starting one the future. Most of the participants want to produce food in organic mode, with significant differences among the countries at study. Most of the participants were enrolled in training activities in agriculture, especially those with higher education. This participation showed significant differences between countries and also according to the dimension of the farms owned by the participants. A significant association was found between being a teacher in forming activities related to agriculture and being a farmer. When compared to distance learning, the training activities in classroom were the most frequented, with significant differences among the countries. Practical implications: This study allowed characterizing the learning activities in the field of organic agriculture and establish direction lines for planning of future training programs, in different countries, with maybe different social, educational and cultural realities Originality/value: Because the study included the participation of people from several countries all around Europe, the results obtained enrich the scientific area of training in Organic Farming, in view of distance learning versus classroom learning on a more global basis.